Growers’ perceptions and attitudes towards fungicide resistance extension services - Olita, Toto; Stankovic, Michelle; Sung, Billy; Jones, Megan; Gibberd, Mark (2024)
Agricultural extension services have been successful in promoting knowledge sharing and innovation in agriculture. However, the adoption of new agricultural practices, particularly in integrated pest management, has been slow. Using a case study with a co-designed survey instrument, this research aimed to understand how growers in the Southwest Western Australian Grainbelt access information and resources to manage fungicide resistance. We found that the growers rely on a combination of paid agronomists, government or research institutes, local grower groups, and field days for fungicide resistance information. Growers seek information from trusted experts who can simplify complex research, value easy-to-understand communication and prefer resources tailored to their local context. Additionally, growers valued information regarding new fungicide developments and having access to rapid fungicide resistance diagnostic services. These findings highlight the importance of providing growers with effective agricultural extension services to manage the risk of fungicide resistance.